2009
DOI: 10.1146/annurev.arplant.043008.092119
|View full text |Cite
|
Sign up to set email alerts
|

DNA Transfer from Organelles to the Nucleus: The Idiosyncratic Genetics of Endosymbiosis

Abstract: In eukaryotes, DNA is exchanged between endosymbiosis-derived compartments (mitochondria and chloroplasts) and the nucleus. Organelle-to-nucleus DNA transfer involves repair of double-stranded breaks by nonhomologous end-joining, and resulted during early organelle evolution in massive relocation of organelle genes to the nucleus. A large fraction of the products of the nuclear genes so acquired are retargeted to their ancestral compartment; many others now function in new subcellular locations. Almost all pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
331
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(336 citation statements)
references
References 151 publications
(191 reference statements)
4
331
1
Order By: Relevance
“…Subsequently, the reorganization of genetic material and regulatory mechanisms, including those pertaining to DNA replication, occurred between the nucleus and the symbiont (Kleine et al, 2009;. Twinkle, an organelle DNA helicase and primase, is shared by plastids and mitochondria in green plants, whereas cyanobacterial dnaB helicase and dnaG primase are conserved in red algae.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the reorganization of genetic material and regulatory mechanisms, including those pertaining to DNA replication, occurred between the nucleus and the symbiont (Kleine et al, 2009;. Twinkle, an organelle DNA helicase and primase, is shared by plastids and mitochondria in green plants, whereas cyanobacterial dnaB helicase and dnaG primase are conserved in red algae.…”
Section: Discussionmentioning
confidence: 99%
“…Early in evolution this has led to the transfer of a large fraction of the mitogenomic information to the nuclear genome. The products of many of these genes are now re-imported while other genes of mitochondrial origin have acquired novel functions elsewhere (Kleine et al, 2009). Recent nuclear inserts of mitochondrial sequences, which occur at surprisingly high rate probably limited by the rates of double strand breaks (Hazkani-Covo et al, 2010), however, give rise to non coding and typically non-functional sequences.…”
Section: Numts: Nuclear Copies Of Mitochondrial Dnamentioning
confidence: 99%
“…There are still debates about the mechanism of DNA transfer from organelles to nucleus and the mode of integration (Leister, 2005;Kleine et al, 2009). It was suggested that the insertion mechanism involves double-strand break repair via NHEJ (Hazkani-Covo and Covo, 2008).…”
Section: Introductionmentioning
confidence: 99%